PERVOMAYSKAYA GRANITE-GNEISS MONOCLINE IN THE SECTION ALONG RIVER SOUTH BUG - Shevchuk, V.; Kravchenko, D.; Mazko, A.; Khabanets, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Pervomayskaya granite-gneiss monocline has been defined as a Paleo-Proterozoic expression of the Pervomaysk fault zone on the base of structural-petrology research. The distribution of different types of tectonites and the zoning structure of granite-gneiss monocline has been shown. The interrelation between deformation processes and granitoid petrogenesis during monocline formation has been revealed.